Colobomatus kimi sp. nov. (Copepoda: Philichthyidae) parasitic in the dwarf goatfish Upeneus parvus Poey, 1852 (Perciformes: Mullidae) in the South Atlantic Ocean - Paschoal, Fabiano; Pereira, Aldenice N.; Luque, José Luis (Zootaxa, 2016)
A new species of copepod, Colobomatus kimi sp. nov., belonging to the cyclopoid family Philichthyidae Vogt, 1877, is proposed based on female specimens collected from the pores of the cephalic sensory system of the dwarf goatfish, Upeneus parvus Poey from the southeastern Brazilian coastal zone. The new species can be distinguished from its closest congeners by the unique combination of characters displayed by the female, including the forked caudal rami, the position of the midventral cephalic process shorter in relation to the lateral cephalic processes, and the presence of paired genital processes. The new species is the first member of Colobomatus Hesse, 1873 found to parasitize mullids of the genus Upeneus